2002
DOI: 10.1590/s0100-29452002000300034
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da necessidade de frio em pessegueiro

Abstract: A necessidade de frio de seis cultivares de pessegueiro [Prunus persica (L.) Batsch] foi estudada em plantas de um e dois anos, em vasos, submetidas a 150; 300; 450 e 600 horas a 2ºC, e em ramos coletados periodicamente em plantas sob condições de frio natural, a campo. Considerando os resultados obtidos nos dois experimentos, estima-se que a necessidade de frio de 'Precocinho' é em torno de 300 horas a 2ºC, equivalente a 150 unidades de frio (UF) pelo modelo de Utah, ou próxima a 200 horas abaixo de 12ºC; par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 7 publications
0
15
0
7
Order By: Relevance
“…However, once the chilling requirement is satisfied, they start blooming, so increasing the likelihood of damage by late winter frost (Citadin et al, 2001), the same occurs in the central-east area of the province of Santa Fe. Nevertheless, Citadin et al (2001) observed that there are varieties of peach trees in Brazil, with high heat requirement for blooming once its chilling requirement has been satisfied, showing adaptation to colder regions (600 CH) as well as to warmer regions (200 CH) (Citadin et al, 2002). In this study, 'Flordaprince' had a similar behaviour; it was the variety with the lowest chilling requirement among the used ones, but it bloomed later, at least ten days after the majority of the low chilling varieties, and only four days before 'Flordaking'.…”
Section: Discussionmentioning
confidence: 99%
“…However, once the chilling requirement is satisfied, they start blooming, so increasing the likelihood of damage by late winter frost (Citadin et al, 2001), the same occurs in the central-east area of the province of Santa Fe. Nevertheless, Citadin et al (2001) observed that there are varieties of peach trees in Brazil, with high heat requirement for blooming once its chilling requirement has been satisfied, showing adaptation to colder regions (600 CH) as well as to warmer regions (200 CH) (Citadin et al, 2002). In this study, 'Flordaprince' had a similar behaviour; it was the variety with the lowest chilling requirement among the used ones, but it bloomed later, at least ten days after the majority of the low chilling varieties, and only four days before 'Flordaking'.…”
Section: Discussionmentioning
confidence: 99%
“…However, 'Biuti' and 'Charme' presented the onset of budburst before flowering. Citadin et al (2002) studied the heritability of the need for heat for anthesis and budburst and examined whether the selection of cultivars with a high heat requirement for flowering tended to delay flowering without delaying the budburst time. Therefore, the behaviour of some cultivars that sprout before flowering is explained by the fact that these cultivars require more heat for flowering than for budburst.…”
Section: Resultsmentioning
confidence: 99%
“…The chill requirement of each cultivar was estimated by calculating the means of the number of hours with temperatures below 12°C from May 1 until the onset of budding for each cultivar in the two years evaluated, as based on the methodology of Citadin, Raseira, Herter, & Silveira, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Dependendo da espécie e da cultivar, temperaturas fora dessa faixa podem atuar positiva ou negativamente na acumulação de horas de frio e a alternância entre temperaturas moderadas e baixas pode aumentar a eficiência das baixas temperaturas (Erez e Couvillon, 1986;Erez et al, 1979;Febvre, 1981). Essas respostas podem apresentar grandes variações entre espécies, na mesma espécie em diferentes anos , entre cultivares (Citadin et al, 2002), entre gemas com idades distintas (Zanette et al, 2000) e em posições distintas dos ramos (Herter et al, 2001).…”
Section: Revisão Bibliográficaunclassified
“…Esse método tem sido utilizado sob dois critérios: 1) a porcentagem de gemas que brotam em um determinado período predeterminado, em geral 3 a 4 semanas, e; 2) na avaliação do tempo necessário para que um determinado estádio de desenvolvimento seja atingido (Dennis, 2003). Outra variação desse método é a utilização de estacas com mais de uma gema, das quais apenas a gema superior é mantida (Carvalho e Zanette, 2004;Citadin, et al, 2002;Putti et al, 2003). Putti et al(2003) afirmam que o fim da paradormência seria detectado pelo início do aumento do número de dias para a brotação e da endodormência pelo início da redução ou estabilização desse número.…”
Section: Revisão Bibliográficaunclassified